Effect of Cobalt and Zinc Precursor Loading on the Catalyst Activity of Fischertropsch Synthesis - Nadia Aida, Che Mustapa (2012)
Five samples of Co-Zn/SBA-15 catalysts were prepared using wet impregnation method with different composition of cobalt loading (5, 10 and 15 wt % Co) and zinc loading (5, 10 and 15 wt % Zn) and were investigated with respect to physical and chemical properties as well influence on activity and selectivity for conversion of H2/CO2 synthesis gas. The catalysts were tested by using Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), N2 Adsorption Analysis (BET) and Thermogravimetric Analyzer (TGA). The feed gas of CO2 instead of CO also had been considered that contributed to product selectivity since cobalt catalyst do not exhibit significantly in Water Gas Shift (WGS) activity and CO2 neither formed nor produced during Fischer Tropsch (FT) synthesis with cobalt catalyst and H2/CO. An investigation of catalytic CO2 hydrogenation into high quality fuels and valuable hydrocarbons was carried out in a glass borosilicate reactor. The operating condition for catalytic testing is at 220 °C and 1 bar using H2/CO2 feed ratios of 3:1. Selectivity of products was depending upon the amount of metal loading constituent as well as the syngas mixture that used. It was found that higher metal loading with optimized promoter loading was the best catalyst for Fischer Tropsch synthesis. It is experimentally found that from the result of gas chromatograph, the conversion of CO2 and product selectivities were calculated. The most efficient catalyst for Ficher Tropsch synthesis is 15% Co/10% Zn-SBA-15. This result was proven by the characteristic of catalyst which is the existance functional groups of cobalt oxides, Si-O-Si, Si-CH3, zinc oxide, OH band, Si-C, and others, higher intensity that indicates higher cobalt dispersion, possess large surface area as well as pore size, small weight loses that indicate thermal stability and having large number of catalyst particles attaching closely with one another that make it more effective during FT process.